Особенности формирования информационной компонентности у студентов педагогических ВУЗов - Камешова, С.С. (My University, 2016)
In the article features of formation of information competence of students of pedagogical universities. Formation of information competence is one of the purposes of education, but at the same time, it means leading the learning process.
Keywords: information competence; formation; professional activity; information resource